Electric-field assisted nucleation processes of croconic acid films. Issue 48 (22nd November 2019) - Yuan, Yifan; Jiang, Xuanyuan; Poddar, Shashi; Xu, Xiaoshan
Abstract : An external electric field can affect the growth dynamics of croconic acid (CA) films, especially the heterogeneous nucleation process, as evidenced by the shift of temperature dependence of the nucleation rate in the electric field. Abstract : Growth of organic thin films using physical vapor deposition typically follows a three-dimensional mode, resulting in a rough surface, which undermines their application potential. To address this issue, we have studied the effect of electric field and temperature on the growth dynamics, especially the heterogeneous nucleation process, of croconic acid (CA) films, taking advantage of the large dipole moment of the molecules and the ferroelectric polarization of the molecular crystals. We found that the nucleation rate reaches the maximum at intermediate temperature, and the electric field shifts the maximum nucleation rate towards lower temperature. An analysis using the classical nucleation theory suggests that the electric field decreases the sublimation temperature, increases the wetting angle, and decreases the surface diffusion barrier. These results provide important insight into the growth of molecular crystal films under electric fields and pave the way to fabricating films with better surface characteristics for molecular ferroelectric films.